Skeptisisme Profesional Auditor dari Sudut Pandang Filsafat Jawa “Ojo Dumeh, Eling lan Waspodo” - Bhilawa, Loggar (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
This study aims to explore and analyze auditors' professional skepticism through the lens of Javanese philosophy, specifically the concepts of